Correlation between the physical activities and the percentage of body fat of the members of fitness center - Miftachurochmah, Yulvia; Budiarti, Ratna; Arjuna, Fatkurahman; Pamungkas, Gallant (Jorpres (Jurnal Olahraga Prestasi), 2024)
Today, a change in lifestyle from active to inactive has begun to occur, especially in the lifestyle of modern society. This research was a correlational study with survey research methods or self-reported questionnaires. The research population was for about 60 members of HSC Fitness Center, Yogyakarta State University taken by a random sampling technique. Meanwhile, the research instrument used to measure the level of physical activity was the Global Physical Activity Questionnaire (GPAQ) developed by the World Health Organization and the percentage of body fat was measured by using the Body Impedance Analysis (BIA) tool. Furthermore, the data analysis was performed by using the Pearson Product Correlation test. The results show that there is a correlation with a significant negative direction on the level of physical activity and body fat percentage of the members of HSC Fitness Center, Yogyakarta State University with a Pearson Product Correlation coefficient of -0.760, and with a significance value of 0.00 < 0.05. Through this research, the research results obtained can be used as information for the wider community, especially those with the excessive body fat percentages so that they pay more attention to their daily physical activities and so they can achieve a healthy body fat percentage.